Sea Surface Temperature and Salinity in Lombok Strait Reconstructed From Coral Sr/Ca and δ18O, 1962–2012 - Genda, Ai; Ikehara, Minoru; Suzuki, Atsushi; Arman, Ali; Inoue, Mayuri (Frontiers in Climate, 2022)
Coral geochemical tracers have been used in studies of the paleoclimatology and paleoceanography of the tropics and subtropics. We measured Sr/Ca and oxygen isotope ratios (δ18O) in a coral sample collected from the southern part of Lombok Strait, a significant outlet of the Indonesian Throughflow (ITF) to the Indian Ocean, to reconstruct the historical record of sea surface temperature (SST) and seawater δ18O. Seawater δ18O can be used to approximate sea surface salinity (SSS) because it reflects the balance of evaporation and precipitation. The resulting time series reconstructed SST and SSS, covering the period 1962-2012, shows no clear trend of global warming, although the record includes a large cooling event (~4℃) during 1996-1997. Although neither SST nor SSS shows systematic relationship with El Nino-Southern Oscillation and Indian Ocean Dipole (IOD), weak but significant correlations are found partly. Additionally, the coral data show signals of major IOD and El Nino events in 1994 and 1997, respectively, although climatic trends recorded in the coral are not consistent with those found along the Java-Sumatra coast. To evaluate other influences on the ITF in Lombok Strait, we compared our coral record with coral records from sites in the Java Sea, the southern part of Makassar Strait, and Ombai Strait. During the northwest monsoon (December-January-February), variations in SST and SSS at Lombok Strait site are similar to those at the Java Sea and southern Makassar sites for the period 1962-1995, which suggests that low-salinity water from the Java Sea is carried at least to the southern part of Makassar Strait where it suppresses the ITF upstream from Lombok Strait. However, the SST and SSS records differ at the three sites during the southeast monsoon (June-July-August), indicating that surface conditions in Lombok Strait vary separately from those in the Java Sea. In the longer term, although global warming has been widely identified in the Indonesian Seas, the coral record shows no clear warming trend in the southern part of Lombok Strait, where fluctuations in the ITF may be modulating the distribution of heat in the surface waters of the western Pacific and eastern Indian Ocean.